Seeing in the dark : the poetry of Phyllis Webb - Butling, Pauline (Wilfrid Laurier University Press, 1997)
"Poet Phyllis Webb initiated new ways of seeing into the cultural "dark" of Western thought. By blurring the axis between "light" and "dark," she redefined women's subjectivity and sexuality, which are traditionally assigned "dark" negative values, in positive terms." "Seeing in the Dark includes perceptive discussions on a number of Webb's collections, specifically Naked Poems, Wilson's Bowl, Water and Light and Hanging Fire. Butling shows how Webb uses strategies of subversion, reversal and re-vision of prevailing traditions and tropes to facilitate "seeing in the dark." She also provides a fascinating analysis of Webb criticism - tracing it over the past thirty years and revealing a shift in critical paradigms. A chapter on biography includes intriguing archival material."--Jacket